Biology teachers' perception of the presence of "botanical blindness" in public schools in the State of Pará (Research, Society and Development, 2021)
The teaching of botany presents several obstacles, among them the students' lack of interest in the content, given the difficulties in realizing the importance of plants for their lives, a condition called “botanical blindness”. This work aimed to understand the perception of biology teachers about the difficulties that high school students have in studying botany, investigating the existence of the condition of “botanical blindness”. In this work, a qualitative and quantitative exploratory sequential research was carried out with 28 teachers of the discipline of biology, working in public high schools in the state of Pará. Structured questionnaires with open and closed questions were used for the data collection and the analysis technique attributed to its interpretation was of the content analysis type. It was identified that 25% of teachers are unaware of the term botanical blindness; the difficulty in perceiving the plants in their environment was the main characteristic of the botanical blindness identified by the professors in their students; the methodologies mentioned by the professors that most aroused the student's interest in botany classes were field classes and practical classes. Teaching should be a moment that provides opportunities for the construction of knowledge in a collaborative way so that all subjects are able to act significantly in this process and the use of different teaching methodologies can contribute to this process, aiming to overcome botanical blindness.